Standardization of health informatics - results and challenges - Klein, G.O. (Yearbook of Medical Informatics, 2002)
A number of standardization initiatives have been in progress for more than ten years in several parts of the world with the aim to facilitate different aspects of the exchange of health information. Important results have been achieved, and in some fields and parts of the world, standards are widely used today. Unfortunately, we are still facing the fact that most healthcare information systems cannot exchange information with all systems for which this would be desired. Either the existing standards are not sufficiently implemented, or the required standards and necessary national implementation guidelines do not yet exist. This causes unacceptable risks to patients, inefficient use of healthcare resources, and sub-optimal development of medical knowledge. This article will review some of the difficulties surrounding standards, as well as highlight the achievements and main global actors, while focusing on the challenges facing the international consensus process.